Theoretical and Experimental Research of Ultra-High-Performance Concrete Tensile Behaviour Based on Micro-Analysis - Liu Xinyi; Zhang Rongling; Duan Yun (The Baltic Journal of Road and Bridge Engineering)
The cracking resistance and durability of the ultra-high-performance concrete (UHPC) structure are directly affected by its tensile behaviour. A micro-analysis method was established to study the tensile behaviour of the UHPC before the appearance of visible cracks. The cooperative characteristic of the steel fibre and the cement matrix was taken as a research focus of the micro-analysis method. The random distribution of steel fibre was considered as normal distribution. Based on the micro-analysis method, the tensile behaviour of UHPC was divided into the elastic stage and micro-damage development stage. Other data sourced elsewhere were used to verify the feasibility of the micro-analysis method and the necessary data were tested using pure bending specimens to verify the theoretical model. The results show that the working mechanism of inner steel fibre can be described by the micro-analysis method. The bending test results of the UHPC at the elastic and the micro-damage development stage match the theoretical model. The tensile behaviour of the UHPC is dominated by the inner steel fibre and the contribution of the cement matrix can be ignored. A bilinear model is proposed to describe the tensile constitutive of UHPC before the appearance of visible cracks, and the limitations of each stage are 8.85 MPa and 12.36 MPa.